Prepositions in their syntactic, semantic, and pragmatic context - Feigenbaum, Susanne; Kurzon, Dennis (Amsterdam ; Philadelphia, PA : J. Benjamins Pub., 2002)
The growing interest in prepositions is reflected by this impressive collection of papers from leading scholars of various fields. The selected contributions of Prepositions in their Syntactic, Semantic and Pragmatic Context focus on the local and temporal semantics of prepositions in relation to their context, too. Following an introduction which puts this new approach into a thematical and historical perspective, the volume presents fifteen studies in the following areas: The semantics of space dynamics (mainly on French prepositions); Language acquisition (aphasia and code-switching); Artif.
Prepositions in their Syntactic, Semantic and Pragmatic Context; Editorial page; Title page; LCC data; Table of contents; Preface; Instability and the theory of semantic forms; Schematics and motifs in the semantics of prepositions; The theoretical status of prepositions; Temporal semantics of prepositions in context; Prepositions and context; Prepositional phrases as noun modifiers in contemporary Hebrew; The Hebrew prepositions mi-/min 'from, of '; A contrastive analysis of French and Hebrew prepositions; A language in change; The French preposition in contact with Hebrew.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Grammar, Comparative and general -- Prepositions; Grammar, Comparative and general -- Syntax; Semantics; Pragmatics; Semantics; Prépositions.; Syntaxe; Sémantique.; Pragmatique; semantics; pragmatics; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Grammar, Comparative and general -- Prepositions; Grammar, Comparative and general -- Syntax; Pragmatics; Semantics; Voorzetsels; Prépositions.; Syntaxe; Sémantique.; Pragmatique; Electronic book